2019
DOI: 10.1111/rda.13585
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related declines in ejaculate quality and sperm kinematics vary among strains of Japanese Quail (Coturnix japonica)

Abstract: For successful breeding programs, it is important to quantify the useful period of a male's reproductive life and it is often done simply by measurement of semen quality. This information is lacking for Japanese quail so we tested whether there is a decline in ejaculate quality and sperm kinematics with age, and whether the decline varies among strains. Nine males (n = 9) from each of 5 strains (A, B, C, D and E) were subjected to 4 semen collections (n = 16 per male) at 8, 16, 26 and 36 weeks of age. Ejaculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…These findings agree with Farooq et al. (2020), who reported that most measures of sperm quality in Japanese quail declined with age. Sperm production peaks around week 16 and decreases as the birds approach 36 weeks of age.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings agree with Farooq et al. (2020), who reported that most measures of sperm quality in Japanese quail declined with age. Sperm production peaks around week 16 and decreases as the birds approach 36 weeks of age.…”
Section: Discussionsupporting
confidence: 93%
“…These data indicated that higher values of semen traits were obtained from 10 to 22 weeks compared with other ages. These findings agree with Farooq et al (2020), who reported that most measures of sperm quality in Japanese quail declined with age.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Semen was collected using teaser female and diluted twofold with collection buffer comprising 150 mM NaCl, 20 mM TES and 35 mM glucose (pH adjusted to 7.40 at 25°C) as described previously (Holm & Wishart, 1998). Sperm concentration was determined by spectrophotometer method as described by Farooq et al (2019). To record sperm motility, samples were prepared as per treatment requirement and motility was recorded in duplicate.…”
Section: Methodsmentioning
confidence: 99%
“…While evidence in supporting senescence to be a widespread phenomenon in nature has been accumulating during the last decade (Nussey et al, 2013), the study of male reproductive senescence has been restricted to a narrower range of species (Lemaître and Gaillard, 2017). Despite this limited taxonomic spectrum, current evidence in humans and captive species of mammals, fish, birds and insects suggests that male age can have profound effects on several traits defining ejaculate and sperm quality (Gasparini et al, 2010;Johnson et al, 2015;Carreira et al, 2017;Herrera-Cruz et al, 2018;Colasante et al, 2019;Fricke and Koppik, 2019;Farooq et al, 2020). For instance, old males have been reported to produce lower ejaculate volume with impaired antioxidant defenses and containing sperm with reduced motility and velocity (Wolf et al, 2000;Sartorius and Nieschlag, 2010;Noguera et al, 2012;Gunes et al, 2016).…”
Section: Introductionmentioning
confidence: 99%